2022
DOI: 10.1007/s43762-022-00053-y
|View full text |Cite
|
Sign up to set email alerts
|

Passengers receptivity of a new public transport mode: case of a BRT project in Lebanon

Abstract: This study examines how far the level of knowledge on a new public transport mode in Lebanon might affect mode choice. Indeed, passenger mode choice is a major issue associated with the effectiveness of new transport projects, as their level of effectiveness and feasibility will depend on the number of new adopters. This investigation is performed by developing mode choice models based on data collected via a questionnaire-based survey. The models were used to compare preferences among private cars, current pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The choice of variables utilized in this survey was based on earlier research with a comparable scope ( 24 , 28 , 54 ). Questions were asked to respondents on their socioeconomic characteristics as well as characteristics of their travel habits.…”
Section: Methodsmentioning
confidence: 99%
“…The choice of variables utilized in this survey was based on earlier research with a comparable scope ( 24 , 28 , 54 ). Questions were asked to respondents on their socioeconomic characteristics as well as characteristics of their travel habits.…”
Section: Methodsmentioning
confidence: 99%
“…The findings highlighted the difficulties the implementing agency faced, which led to a switch from BRT to a regular bus. According to the information gathered from a questionnaire-based survey, Al-Shaar et al ( 2022 ) created mode choice models to investigate how much knowledge of a new public transportation option in Lebanon would influence mode choice. This study demonstrated the importance of taking into account people's perceptions of new modes of transportation as well as their level of familiarity with older ones when conducting feasibility assessments for any transportation projects in developing nations.…”
Section: Literature Reviewmentioning
confidence: 99%